Near-Fault Response and Loading Protocols of Box Columns in Steel Frames with Self-Centering Braces to Provide Recentering Capability - Yu-Fang Liu; Chung-Che Chou; Chia-Ying Chung; Hao-Che Huang (Advances in Civil Engineering)
The main objective of this study was to establish loading protocols for self-centering braced frames (SCBFs) while taking into account the impact of near-fault ground motions. SCBFs are self-centering frames that have lower residual drift than buckling-restrained braced frames (BRBFs) under near-fault earthquakes; thus, SCBFs can better control damage to buildings. Typically, first-story columns are employed to represent the seismic behavior of a structure; therefore, loading protocols were developed for first-story columns in SCBFs under near-fault earthquakes. Nonlinear static and dynamic analyses of SCBFs designed with various periods were conducted for better understanding the seismic performance of SCBFs. Finally, the loading protocols developed for SCBFs were compared with those for BRBFs under the same near-fault motions.